(3GdCdajI aj GdfMhs - (3GdWGFj, GdCfOdSj, GdLjGfj, GHf eGdc, LeGd GdOjf, eMeO Hf YHO Gddg Hf eGdc, J (B672 (3g`s
(3ChdgG (B:s
(3bGd eMeO gh GHf eGdc (B*** (3CMeO QHj Gddg NjQ eGdc , eUdjG Ydi GdQShd GdeUWai (B*** (3hBdg GdeSJcedjf GdTQaGs
(3BNQgG (B:s
(3CMUQ ef GdcGajI GdNdGUI (B*** (3ceG GbJVi ZfG HdG NUGUI , hCMeO Gddg eUdjG Ydi (B*** (3eMeO NjQ fHj CQSdG , hBdg GdZjQ GdcQGe GdHQQI (B*** (3hUMHg GdefJNHjf GdNjQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 233s
(3eYLe GdeDdajf(B: 3 / 450s
(3cTa GdXfhf(B: 1 / 151s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs